Citizen resistance to the nepotism politics of the Head of Pulau Tinggi Village - S., Zulian; Winarno, Winarno; Rasyid, Machmud Al (Indonesian Journal of Multidisciplinary Science, 2024)
This study aims to examine how village heads carry out nepotism politics against citizens in high island villages and how citizens in high island villages carry out resistance politics in the face of high island village head nepotism politics. The research method used is qualitative with a Case Study strategy. This study seeks to find the politics of nepotism carried out by the village head and the politics of resistance used by citizens in the high island village. The results showed that the politics of nepotism carried out by the village head was a form of support given to his family in the election that occurred in the high island village. Citizen Resistance to Nepotism Politics of the Head of Pulau Tinggi Village in holding elections was carried out due to citizens' awareness of participation in democracy.